2017
DOI: 10.1371/journal.pone.0182005
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers’ perceptions of point-of-care testing in a low-income country—A qualitative study in Southwestern Uganda

Abstract: BackgroundPoint-of-care (POC) tests have become increasingly available and more widely used in recent years. They have been of particular importance to low-income settings, enabling them with clinical capacities that had previously been limited. POC testing programs hold a great potential for significant improvement in low-income health systems. However, as most POC tests are developed in high-income countries, disengagement between developers and end-users inhibit their full potential. This study explores per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 42 publications
(51 reference statements)
5
53
0
Order By: Relevance
“…With respect to clinical management, professional nurses felt that a same-day CD4 test result would facilitate patient readiness, adherence to ART, and fewer follow-up visits. We concur with findings from two qualitative studies, one from South Africa [39] and the other from Uganda [40], where healthcare workers found that POC testing resulted in earlier interventions and reduced burden of patient clinic visits. Only a minority in this study felt that they needed extra assistance and further training and education.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to clinical management, professional nurses felt that a same-day CD4 test result would facilitate patient readiness, adherence to ART, and fewer follow-up visits. We concur with findings from two qualitative studies, one from South Africa [39] and the other from Uganda [40], where healthcare workers found that POC testing resulted in earlier interventions and reduced burden of patient clinic visits. Only a minority in this study felt that they needed extra assistance and further training and education.…”
Section: Discussionsupporting
confidence: 89%
“…HCPs have expressed confidence in the POCT NAAT results, and treating patients on this basis . They mentioned that POCTs provide an opportunity for targeted patient treatment, immediate partner notification and reduced follow‐up effort .…”
Section: Resultsmentioning
confidence: 99%
“…They mentioned that POCTs provide an opportunity for targeted patient treatment, immediate partner notification and reduced follow‐up effort . However, the main barriers indicated were the long waiting time, the time consumed in the documentation process, sample collection, inadequate training and the limited availability of POCTs due to a high unit cost per test .…”
Section: Resultsmentioning
confidence: 99%
“…None of our participants mentioned POCTs as a means to rule out serious infections36 nor that POCTs would enable better access to alternative diagnostic methods where laboratory access was inadequate 39 40. Clinicians in our study were less convinced about whether POCTs would provide more efficient care and fewer consultations.…”
Section: Discussionmentioning
confidence: 65%
“…Interviews followed a topic guide (online supplementary appendix), which included exploratory questions about how the management of common infections could be improved and to gauge clinicians’ ideas about a new (hypothetical) POCTs that could support clinical decision-making. Interview questions were informed by studies done in HIC settings, and adapted after advice from clinicians practising in the Western Cape Metro and in response to emerging data 34–40. Participants were asked about their experience of existing POCTs, and their opinions of new POCTs for the specified two common infection syndromes.…”
Section: Methodsmentioning
confidence: 99%